Interview with Hannah Berry. Issue 1 (1st March 2021) - Miller, Ann
Abstract: In this interview, the Brighton-based comics artist Hannah Berry discuses her current role as Comics Laureate, which has included the commissioning of a survey into the conditions of work of comics artists in the United Kingdom and has demonstrated the financial hardship that most of them endure. She also talks about the importance of mentoring, organising work around childcare, and how she came to produce a weekly strip for the New Statesman . The interview then focuses on Berry's three published graphic novels, touching on the influence of films, the tension between storytelling and play with the codes of the medium, the use of gutters and text as elements in a horror story, comics as a corrective to fake news, and the political research that underlies satire.